THE INFLUENCE OF SERVICE QUALITY AND TRUST ON CUSTOMER LOYALTY WITH SATISFACTION AS AN INTERVENING VARIABLE IN MANDIRI SUPERMARKET MEDAN - May Friska Yuliani Saragih; Yeni Absah; Endang Sulistya Rini (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Customer Trust has a positive and significant effect on Customer Loyalty at Mandiri Supermarket Griya Medan. Customer Satisfaction has a positive and significant effect on Customer Loyalty at Mandiri Supermarket Griya Medan. Service Quality has a positive and significant effect on Customer Satisfaction at Mandiri Supermarket Griya Medan. significantly to Customer Satisfaction able to mediate the effect. Service Quality on Customer Loyalty. Customer Satisfaction is able to mediate the influence of Customer Trust on Customer Loyalty. Service Quality has a positive and significant effect on Customer Satisfaction at Mandiri Supermarket Griya Medan. Customer Trust has a positive and significant effect on Customer Satisfaction being able to mediate the effect. Service Quality on Customer Loyalty. Customer Satisfaction is able to mediate the influence of Customer Trust on Customer Loyalty. Service Quality has a positive and significant effect on Customer Satisfaction at Mandiri Supermarket Griya Medan. Customer Trust has a positive and significant effect on Customer Satisfaction being able to mediate the effect. Service Quality on Customer Loyalty. Customer Satisfaction is able to mediate the influence of Customer Trust on Customer Loyalty.